Factors affecting the retention of generation Y black women in the finance sector in Johannesburg, South Africa - Dhlomo, Monhlanhla Happiness (My University, 2018)
The world of work has changed over the years because of globalisation and new ways of doing business. In order for organisations to remain competitive in the market, they need to adapt to these changes by ensuring that they attract, develop and retain the right talent. This is particularly acute amongst South African organisations as they need to retain the right talent due to skills shortages and employee mobility. The issue of skills shortages is a result of black people not being given a good education and opportunities in the past during apartheid (IDASA, 1995). Also, now that there has been improvement made with giving the historically disadvantaged (i.e. black men and women) preference with regard to employment in South Africa, this has created opportunities to move and change jobs. Hence, this research explored factors that contribute to the retention of employees in the South African context. It specifically looked at Generation Y black female professionals from the ages of 25 to 35 years old working in the finance sector. The reason for this is because Generation Y, in comparison to other generations (i.e. Baby Boomers and Generation X), are currently those who are mostly employed. As much as affirmative action has made progress in giving the disadvantaged preference with regards to employment and empowering women by giving them more opportunities in the workplace then men, black women are still not developed and promoted in the workplace as they should be. This has led to organisations being challenged by the legislation to develop and promote black women in the workplace. Also, this gives black women more opportunities to constantly seek for better jobs and hop from one job to the next. This has created a challenge for organisations to retain them. Furthermore, the industries that have a high turnover according to Statistics SA (2016) and Compdata Surveys (2016) are finance, mining and manufacturing, with the highest being finance. A qualitative research design was used to explore factors that contribute to the retention of Generation Y black female professionals. The results showed compensation, work/organisational environment in relation to career development opportunities, gender inequality/discrimination, racism, lack of support, mentorship, harassment, work overload, reward and recognition, and work-life balance as challenges that Generation Y black female professionals face in the workplace. These also showed as factors that have an impact on the retention of Generation Y black female professionals. Also, the results showed that these challenges and factors have a psychological and professional impact on Generation Y black female professionals. Recommendations on the strategies that organisations can implement to improve the retention of Generation Y black female professionals are discussed. Suggestions ii to improve future research on the retention of Generation Y black female professionals are also discussed.
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Master of Commerce (Human Resource Management), Johannesburg 2018
Keywords: Women--Employment; Sex discrimination against women--South Africa; Blacks--South Africa